Effect of regional medical disparities on complications in patients with hypertension: Cox’s proportional hazard models - Yun, Choa; Park, Minah; Joo, Jae Hong; Kang, Soo Hyun; Jeong, Sung Hoon; Nam, Chung-Mo; Park, Eun-Cheol; Jang, Sung-In (Frontiers in Medicine, 2023)
Objective: Complications associated with hypertension can be alleviated by providing necessary medical services. However, there may be disparities in their provision depending on regional differences. Thus, this study aimed to examine the effects of regional healthcare disparities on complications in patients with hypertension in South Korea. Methods: Data from the National Health Insurance Service National Sample Cohort (2004–2019) were analyzed. The position value for the relative composite index was used to identify medically vulnerable regions. The diagnosis of hypertension within the region was also considered. The risk of complications associated with hypertension included cardiovascular, cerebrovascular, and kidney diseases. Cox proportional hazards models were used for statistical analysis. Results: A total of 246,490 patients were included in this study. Patients who lived in medically vulnerable regions and were diagnosed outside their residential area had a higher risk of complications than those living in non-vulnerable regions and were diagnosed outside the residential area (hazard ratio: 1.156, 95% confidence interval: 1.119–1.195). Conclusion: Patients living in medically vulnerable regions who were diagnosed outside their residential areas were more likely to have hypertension complications regardless of the type of complication. Necessary policies should be implemented to reduce regional healthcare disparities.